Rhizomatic Resurgence: Multispecies Storytelling and Ecological Entanglement in Southeast Asian Bio-Art - Jasmila Tanjung; Matilda Munoz; Sarah Armalia; Kevin Setiawan; Sudarto Sudarto (Enigma Institute, 2025)
The Anthropocene epoch has catalyzed a profound shift in contemporary art, with Bio-Art emerging as a critical field for interrogating the complex relationships between humanity, technology, and the non-human world. While significant scholarship has explored Bio-Art in Western contexts, its unique manifestations within Southeast Asia remain underexamined. This study investigated the rise of a specific mode of Bio-Art in this region, characterized by rhizomatic structures, multispecies storytelling, and deep ecological entanglement, offering a vital counter-narrative to anthropocentric perspectives. This research employed a qualitative, multi-sited case study methodology. Four exemplary Bio-Art projects from Indonesia, Thailand, Philippines, and Singapore, created between 2020 and 2024, were purposively selected. A multi-modal analytical approach was utilized, combining formal visual analysis of the artworks, critical discourse analysis of artist statements and curatorial texts, and thematic analysis of semi-structured interviews with the artists and curators. The analysis was theoretically grounded in the concepts of the rhizome (and multispecies ethnography. The analysis revealed four dominant themes. First, artists consistently employed the rhizome as both method and metaphor, creating non-linear, decentralized works that mirrored ecological networks. Second, a significant pattern of weaving technoscience with traditional ecological knowledge (TEK) was identified, where advanced biotechnologies were syncretized with local cosmologies and indigenous practices. Third, the artworks actively engaged in more-than-human narration, displacing the human as the central protagonist and instead foregrounding the agency of fungi, plants, microbes, and other organisms. Finally, these projects cultivated affective ecologies, generating powerful emotional responses in viewers to foster critical engagement with pressing regional issues. In conclusion, Southeast Asian Bio-Art, as examined in this study, represents a significant